CCAFS South Asia Climate-Smart Agriculture Learning Platform Newsletter, October 2013 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CCAFS South Asia Climate-Smart Agriculture Learning Platform is a quarterly newsletter that features research highlights and field stories from CCAFS’ work in the South Asia region. In this edition, read about how our train-the -trainer workshops have resulted in more women leaders becoming advocates for climate change adaptation. By partnering with the Nepal Development Research Institute, CCAFS has reached nearly a million listeners of Radio Nepal with short jingles on climate change and climate smart agriculture. Practical Action, Nepal, is implementing the CCAFS Climate-Smart Village model after winning a grant to scale out climate smart agriculture